Association of High Sensitivity C-Reactive Protein in Polycystic Ovary Syndrome (Journal of Dhaka Medical College, 2023)
Objective: This study is aimed to see the level of high sensitivity C-reactive protein (hs-CRP) and its association with manifestations of polycystic ovary syndrome (PCOS).Design: This cross-sectional study was conducted over a period of one year (January 2017 to December 2018) in the department of Endocrinology of a University hospital.Participants: Fifty-five PCOS patients diagnosed on basis of revised Rotterdam diagnostic criteria 2003 and 50 age-matched healthy controls [PCOS vs. Control- BMI (kg/m2): 25.47±4.65 vs. 20.68±3.51, p5 mg/L) was found significantly higher in them than that of controls; but only in non-obese (BMI